2019
DOI: 10.1007/s00068-019-01145-x
|View full text |Cite
|
Sign up to set email alerts
|

A proposed amendment to the current guidelines for mild traumatic brain injury: reducing computerized tomographies while maintaining safety

Abstract: Purpose Head trauma is a common complaint in emergency departments. Identifying patients with serious injuries can be difficult and generates many computerized tomographies. Reducing the number of computerized tomographies decreases both cost and radiation exposure. The aim of this study was to evaluate whether the current Scandinavian Neurotrauma Committee guidelines could be revised in such a way that would enable hospitals to perform fewer computerized tomographies while maintaining the ability to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Subsequently, a small but not negligible number of patients experience long-term disability or die due to intracranial complications. As the outcome depends on timely diagnosis and appropriate treatment of intracranial lesions [ 10 , 11 ], several guidelines have been developed to identify patients that can safely be discharged from those with a need for a CCT scan as the reference diagnostic tool [ 4 , 5 , [12] , [13] , [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, a small but not negligible number of patients experience long-term disability or die due to intracranial complications. As the outcome depends on timely diagnosis and appropriate treatment of intracranial lesions [ 10 , 11 ], several guidelines have been developed to identify patients that can safely be discharged from those with a need for a CCT scan as the reference diagnostic tool [ 4 , 5 , [12] , [13] , [14] , [15] , [16] ].…”
Section: Introductionmentioning
confidence: 99%
“…Its short half-life time of 60–120 min restricts the analysis to patients presenting within 6 h after injury [ 4 , 23 ]. Due to its high negative predictive value (NPV) of 99% for normal CCT findings [ 17 ], it has been included into few guidelines as pre-head CT screening test [ 12 , 13 , 17 ]. While it has been demonstrated that substantial reduction of CT scans is achieved by implementing these guidelines [ 15 , 24 ], S100B testing has not been widely adopted as a routine by ED-physicians yet.…”
Section: Introductionmentioning
confidence: 99%
“…This is time-consuming, expensive and exposes the patient to potentially harmful radiation [ 14 , 15 ]. The annual ED influx of head-trauma patients is substantial [ 7 , 21 , 25 ]. Even small improvements in the clinical management that lead to decreased processing time, decreased use of radiation and/or decreased cost due to the use of brain biomarkers and other diagnostic tools, such as microwave machines, would benefit the health care system and patients alike [ 7 , 21 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study will be set at Helsingborg General Hospital, Helsingborg, Sweden. The hospital has a catchment area of 300,000 people and approximately 75,000 ED visits per annum with 1800 isolated TBI patients and another 1000 multi-trauma patients [ 25 ]. The SNC Guideline is the hospital recommended guideline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation